Comparability of hemoglobin concentration measurements from the HemoCue Hb201+ and Hb801 in birds and a mammal with and without nucleated red-blood cells - Kevin G McCracken; Haley B Johnston; Katherine A McCracken; Riley M Olson; Jose Antonio Otero Soberon; Renzo Hernan Turpo Aroquipa; Luis Alza (Journal of Field Ornithology, 2024)
HemoCue analyzers are standard point-of-care devices for measuring blood hemoglobin concentration ([Hb]). The utility of these photometers has been demonstrated for all vertebrate lineages including birds, yet because most vertebrates except mammals possess nucleated red-blood cells, their [Hb] readings are inflated upward in these taxa and require a correction factor relative to the reference calibration. We field tested the newest of these analyzers, Hb801, against its predecessor, the Hb201+. Because of differences in the photometry methods, these two analyzers were not found to be equivalent for taxa with nucleated red-blood cells, such as birds. Whereas a correction factor of 1.0–1.4 g/dL is required for the Hb201+, it may be that no correction factor is required for the Hb801. Further study of the Hb801 relative to a gold-standard reference in non-mammalian lineages is warranted.